Study of regionalization of the northern parts of Sweden 2008 - Lidström, Anders (Umeå University, 2011)
In order to capture the views that the citizens in the northern parts of Sweden hold on regionalization and their opinions about the preconditions for development in the north, a citizen survey was carried out from September 2008. Among the citizens in the four northernmost counties, 4000 respondents have been randomly selected to take part in the survey. The questionnaire includes questions on territorial identities, regionalization, democracy, health care, regional development and consequences of globalization. Different versions of the questionnaire have been developed for each of the two new regions. The timing and to some extent also the questions have been coordinated with corresponding studies being carried out in the regions of Västra Götaland and Skåne by the SOM-institute at Göteborg University in order to make it possible to compare regionalization in the south, the west and the north in Sweden.

Syftet med enkäten är att fånga in medborgarnas perspektiv på utvecklingsförutsättningar och samhällsliv i norr. Formuläret innehåller frågor om bl.a. hemmahörighet och identitet, regionalisering och demokrati, lokala och regionala utvecklingsförutsättningar, hälso- och sjukvård samt hur man ser på globaliseringen. Enkäten har utformats i två versioner för de boende i var och en av de båda planerade regionerna, eftersom några frågor är specifika för resp region. Undersökningens genomförande och till en del även frågornas innehåll har samordnats med liknande undersökningar i Skåne och Västra Götaland. Avsikten är att därigenom göra det möjligt att jämföra regionaliseringarna i södra, västra och norra Sverige. Tanken är också att denna studie skall kunna följas upp med liknande undersökningar framöver för att kunna analysera förändringar över tid i fråga om t.ex. regional identitet och demokrati.
Norrländsk regionstudie 2008
Keywords: regionalism; regionalism; national identity; nationell identitet; community identification; medborgaridentitet; globalization; globalisering; internal politics; inrikespolitik; Health care services and policies; Hälso- och sjukvårdstjänster och -politik; Social behaviour and attitudes; Socialt beteende och attityder; Cultural and national identity; Kulturell och nationell identitet; Social Sciences; Samhällsvetenskap